(untitled) (Homoeopathy for All, 2022)
India is considered, now-a-days, as the world leader in Homoeopathy. A large percentage of the population of the country uses Homoeopathic medicines mainly because of its cost, effectivity and safety having least side effect. Apart from India, Homoeopathy is practiced in a number of European, North American and Latin American countries where popularity of Homoeopathy is growing, but till to day India is the market leader in Homoeopathy. By the year 2024 it is expected that more than 3 lac Homoeopaths will be practicing with Homoeopathic medicines in the country which will naturally generate a substantial revenue for the Government. The growth of Homoeopathic pharma industry per annum is expected to be around 20%. But the sector has the potentiality to grow at a faster rate if it gets sufficient Governmental help. The Government may support the industry actively: